Some form of insanity or other psychic infirmity: Canons 1041, 1° and 1044, §2, 2° - Woestman, William H. (Roman replies and CLSA advisory opinions 1995, 1995)
According to canon 1044, §2, 2°, a cleric afflicted with some form of insanity or other psychic infirmity mentioned in canon 1041, 1° is impeded from exercising orders. Is a pedophile impeded from exercising orders by this prescription of the code?